2018
DOI: 10.1097/prs.0000000000004828
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Ketorolac Use and Postoperative Hematoma Formation in Reduction Mammaplasty: A Single-Surgeon Experience of 500 Consecutive Cases

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…About 30 minutes prior to completion of the procedure, our institution's specified maximum safe volume of 0.25% bupivacaine hydrochloride with epinephrine is infiltrated subfascially (up to 150 mg if patient weight is ≥60 kg or 1 ml/kg of weight if patient weight is <60 kg), and a dose of intravenous acetaminophen and ketorolac is given unless medically contraindicated. Although some studies have suggested an elevated risk of hematoma formation with ketorolac in patients undergoing reduction mammaplasty, our data do not demonstrate this association (Firriolo et al, 2018).…”
Section: Timing and Techniquecontrasting
confidence: 99%
“…About 30 minutes prior to completion of the procedure, our institution's specified maximum safe volume of 0.25% bupivacaine hydrochloride with epinephrine is infiltrated subfascially (up to 150 mg if patient weight is ≥60 kg or 1 ml/kg of weight if patient weight is <60 kg), and a dose of intravenous acetaminophen and ketorolac is given unless medically contraindicated. Although some studies have suggested an elevated risk of hematoma formation with ketorolac in patients undergoing reduction mammaplasty, our data do not demonstrate this association (Firriolo et al, 2018).…”
Section: Timing and Techniquecontrasting
confidence: 99%
“…38,75,78 This fear persists despite studies showing no difference in bleeding risk in adults 44 and children 11,61 undergoing cranial surgery. Similar investigations in orthopedics, 81 spinal surgery, 18 plastic surgery, 59 general surgery, 23 otolaryngology, 7 and other major surgeries 24 have affirmed the safety of postoperative NSAID use, as well as a meta-analysis of 27 studies with 2314 patients across a range of disciplines. 26 Although not directly comparable, the pediatric literature has also shown safety in postoperative NSAID use in children undergoing surgery.…”
Section: Safety Of the Opioid-sparing Protocol In Cranial Surgerymentioning
confidence: 77%
“…However, the use of ketorolac in reduction mammaplasty patients has been controversial because of fear of increased hematoma risk. Two studies 85,86 found only a slightly increased risk of hematoma associated with perioperative ketorolac that was nonsignificant in otherwise healthy patients. Two additional studies 87,88 showed a minimally increased risk of developing a hematoma after reduction mammaplasty in women who were administered perioperative ketorolac.…”
Section: Rationalementioning
confidence: 98%